The role of glutamate signaling in incentive salience: second‐by‐second glutamate recordings in awake Sprague‐Dawley rats. Issue 4 (15th May 2018) - Batten, Seth R.; Pomerleau, Francois; Quintero, Jorge; Gerhardt, Greg A.; Beckmann, Joshua S.
Abstract: The attribution of incentive salience to reward‐predictive stimuli has been shown to be associated with substance abuse‐like behavior such as increased drug taking. Evidence suggests that glutamate neurotransmission and sequential N‐methyl‐D‐aspartate (NMDA) activation are involved in the attribution of incentive salience. Here, we further explore the role of second‐by‐second glutamate neurotransmission in the attribution of incentive salience to reward‐predictive stimuli by measuring sign‐tracking behavior during a Pavlovian conditioned approach procedure using ceramic‐based microelectrode arrays configured for sensitive measures of extracellular glutamate in awake behaving Sprague‐Dawley rats. Specifically, we show that there is an increase in extracellular glutamate levels in the prelimbic cortex (PrL) and the nucleus accumbens core (NAcC) during sign‐tracking behavior to a food‐predictive conditioned stimulus (CS+) compared to the presentation of a non‐predictive conditioned stimulus (CS−). Furthermore, the results indicate greater increases in extracellular glutamate levels in the PrL compared to NAcC in response to the CS+, including differences in glutamate release and signal decay. Taken together, the present research suggests that there is differential glutamate signaling in the NAcC and PrL during sign‐tracking behavior to a food‐predictive CS+. Abstract : The attribution of incentive salience to reward‐predictive stimuli has been shown to be associated with substance abuse‐like behavior such as increased drug taking. We use a novel electrochemical technology to show that differential glutamate signaling occurs in the nucleus accumbens core and prelimbic cortex in freely‐moving rats exhibiting sign‐tracking behavior in a Pavlovian conditioned approach procedure. Overall, our data suggest that glutamate signaling in the nucleus accumbens core and prelimbic cortex are important in incentive salience, providing more evidence supporting the importance of glutamatergic signaling underlying behavior associated with substance abuse. Abbreviations: conditioned stimulus plus (CS+), conditioned stimulus minus (CS−).